Influencing factors of three pronuclei incidence and their impact on pregnancy outcomes in women with good prognosis undergoing conventional in vitro fertilization with donor sperm: a retrospective cohort study - Jianhua Sun; Xiang Liu; Shengjia Shi; Mingzhao Li (Frontiers in Reproductive Health)
PurposeThis study aimed to investigate the influencing factors of three pronuclei (3PN) zygote incidence and their impact on pregnancy outcomes in women with good prognosis undergoing conventional in vitro fertilization with donor sperm (C-IVFD).MethodsThis retrospective study included women aged 35 years or younger who underwent the long/ultra-long follicular phase agonist protocol between January 2014 and January 2021. C-IVFD cycles were divided into the 3PN = 0% group (no 3PN zygotes) and the 3PN > 0% group (with 3PN zygotes). Multivariate logistic regression analysis was performed to identify factors influencing 3PN zygote incidence. The primary outcomes were clinical pregnancy, ongoing pregnancy, abortion and live birth rates. The secondary outcomes were cleavage, high-quality embryo, available embryo, implantation and ectopic pregnancy rates.Results1,250 embryo transfer cycles were included in this study. The peak estradiol (E2) level on the day of human chorionic gonadotrophin (hCG) administration (OR: 1.16, 95% CI 1.12–1.19, p < 0.001) and the number of retrieved oocytes (OR: 1.08, 95% CI 1.05–1.11, p < 0.001) were independently associated with 3PN incidence. Compared to the 3PN > 0% group, the 3PN = 0% group exhibited significantly higher ongoing pregnancy rates (p = 0.033) and live birth rates (p = 0.009), as well as lower abortion rate (p = 0.026). No significant differences were found between the 3PN = 0% and 3PN > 0% groups in cleavage, high-quality embryo, available embryo, implantation and ectopic pregnancy rates (p > 0.05).ConclusionsThe peak E2 level on hCG administration day and the number of retrieved oocytes were independently associated with 3PN incidence. The incidence of 3PN zygotes has a negative impact on pregnancy outcomes in women with good prognosis undergoing C-IVFD.